Clinicopathological features and management of gastric cancer in Port Harcourt - Manuel, Amabra Dodiyi; Danagogo, Okigbeye (International Surgery Journal, 2020)
Background: Gastric cancer is a relatively common cancer and has been documented as the 5th commonest cancer worldwide and the 3rd leading cause of cancer death. Surgery is the treatment of choice for operable cases while chemotherapy. It has a poor prognosis with a relative overall 5-year survival rate of 18%. Methods: This is a retrospective study of all patients that presented with gastric cancer to University of Port Harcourt Teaching Hospital between 1st January 2008 to 31st December 2017. Data were extracted and analyzed using the Statistical Package for Social Sciences (SPSS). Results: There were 14 males and 12 females seen within the study period making a male to female ratio of 1.2:1. Their ages ranged from 35 to 75 years with a mean of 54.7±4.8 years. The peak age incidence is in the 61-70-year age range. Four patients had curative surgery (D2 sub total gastrectomy) while 6 patients (23.1%) had D1 sub total gastrectomy. Post-operative complications occurred in 7 patients (26.9%). And the commonest was surgical site infection, seen in 4 patients (15.4%). Three patients died giving a mortality rate of 11.5%. Conclusions: Most patients with gastric cancer present with advance disease. The choice of treatment should be based on patient’s fitness, survival benefit and after an accurate assessment of extent of disease.